(untitled) (Educational Dimension, 2025)
This study investigates the effectiveness of pedagogical conditions for developing soft skills among future officers of the National Guard of Ukraine (NGU) during wartime. Through a mixed-methods approach combining quantitative and qualitative methodologies, we examined the development of essential military leadership competencies in a 12-month pedagogical experiment at the Kyiv Institute of NGU. The study involved 132 participants divided into experimental (n=64) and control (n=68) groups, with the experimental group receiving enhanced soft skills training through specialized pedagogical interventions. Results demonstrate significant improvements in the experimental group across multiple competency areas, including communication skills (31% increase), critical thinking (23%), teamwork (31%), lifelong learning (64%), professional ethics (31%), and leadership abilities (33%). Statistical analysis using the χ2 criterion confirmed the significance of these improvements at the 0.05 level. The findings suggest that structured pedagogical interventions, particularly those integrating combat experience and mentorship approaches, can effectively enhance military officers’ soft skills development. This research contributes to the growing body of evidence supporting the importance of systematic soft skills training in military education, especially during periods of active conflict. The study’s implications extend beyond the Ukrainian context, offering insights for military education programs globally while highlighting the need for continued research into long-term skill retention and cross-cultural applications.